Liquid‐Phase Electrochemical Scanning Electron Microscopy for In Situ Investigation of Lithium Dendrite Growth and Dissolution. Issue 13 (27th January 2017) - Rong, Genlan; Zhang, Xinyi; Zhao, Wen; Qiu, Yongcai; Liu, Meinan; Ye, Fangmin; Xu, Yan; Chen, Jiafan; Hou, Yuan; Li, Wanfei; Duan, Wenhui; Zhang, Yuegang
Abstract : An in situ electrochemical scanning electronic microscopy method is developed to systematically study the lithium plating/stripping processes in liquid electrolytes. The results demonstrate that the lithium dendrite growth speed and mechanism is greatly affected by the additives in the ether‐based electrolyte.